2004
DOI: 10.1172/jci20425
|View full text |Cite
|
Sign up to set email alerts
|

Dysbindin-1 is reduced in intrinsic, glutamatergic terminals of the hippocampal formation in schizophrenia

Abstract: Eleven studies now report significant associations between schizophrenia and certain haplotypes of singlenucleotide polymorphisms in the gene encoding dysbindin-1 at 6p22.3. Dysbindin-1 is best known as dystrobrevin-binding protein 1 (DTNBP1) and may thus be associated with the dystrophin glycoprotein complex found at certain postsynaptic sites in the brain. Contrary to expectations, however, we found that when compared to matched, nonpsychiatric controls, 73-93% of cases in two schizophrenia populations displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(169 citation statements)
references
References 67 publications
11
156
2
Order By: Relevance
“…It is thus likely that the BLOC-1-dependent pathway that we have defined is ubiquitous in mammals, but it has been exploited by specialized cell types for delivery of specific cargo to LROs, such as melanosomes, platelet dense granules, and lung lamellar bodies, and/or to synaptic vesicles (McGarry et al, 2002;Talbot et al, 2004;Bray et al, 2005;Guttentag et al, 2005). Our data suggest that at least one critical cargo protein is targeted from early endosomes to each of these organelles in a BLOC-1-dependent manner.…”
Section: Discussionmentioning
confidence: 75%
“…It is thus likely that the BLOC-1-dependent pathway that we have defined is ubiquitous in mammals, but it has been exploited by specialized cell types for delivery of specific cargo to LROs, such as melanosomes, platelet dense granules, and lung lamellar bodies, and/or to synaptic vesicles (McGarry et al, 2002;Talbot et al, 2004;Bray et al, 2005;Guttentag et al, 2005). Our data suggest that at least one critical cargo protein is targeted from early endosomes to each of these organelles in a BLOC-1-dependent manner.…”
Section: Discussionmentioning
confidence: 75%
“…However, these multipotent proteins have roles in multiple biological pathways that affect normal brain development as well as cognitive functions in the matured brain, and may contribute to a common pathophysiological 'lesion' that settles in after establishment of the illness. A common theme for DISC1, neuregulin1, and PSD95 is that manipulating these gene products impacts neuroplasticity, a core feature of the schizophrenia syndrome (McCullumsmith et al, 2004;Talbot et al, 2004).…”
Section: The Schizophrenia Phenotypementioning
confidence: 99%
“…We observed the total expression of dysbindin-1 and NRG-1 (that is, the combined expression of all isoforms), which had previously been observed in a postmortem brain, 12,[14][15][16] to determine whether immortalized lymphocytes are a good tool to determine the effect of genetic risks of dysbindin-1 and NRG-1 on their expression and whether immortalized lymphocytes are an appropriate alternative to neuronal tissue.…”
Section: Introductionmentioning
confidence: 92%
“…13 Expression studies in postmortem brains have also revealed lower expression of dysbindin-1 and higher expression of NRG-1 type I, in subjects with schizophrenia. 12,[14][15][16] Postmortem brain tissues are necessary for determining the pathophysiology of schizophrenia. Many gene expression studies have been conducted using postmortem brain tissues.…”
Section: Introductionmentioning
confidence: 99%